Conversing with Readers in Aunt Judy’s Magazine: Building a Community of Young Middle-Class Philanthropists to Fight the ‘Grim Nurses’ - Matthew Dunleavy (Cahiers Victoriens et Edouardiens)
Under the editorship of Margaret Gatty (1809-1873)—an amateur naturalist and the author of several didactic fairy-stories—a new monthly, six-penny magazine was launched in 1866: Aunt Judy’s Magazine. By the time of its first issue, the Hospital for Sick Children at Great Ormond Street (GOSH) had already been serving impoverished children for fourteen years. Dr Charles West founded the hospital in 1852 and it quickly became popular with philanthropists, most notably, in the early years, Charles Dickens who described the hospital as counteracting the destructive effects of the ‘Grim Nurses: Poverty and Sickness’. Shortly after the founding of the magazine, in 1868, ‘Aunt Judy,’ the editorial persona used in the magazine, used the rapport she had built up with her child readers to encourage them to donate to GOSH. The magazine and its readers would go on to raise thousands of pounds in individual donations and monthly, quarterly, and annual subscriptions to establish several ‘Aunt Judy’s Cots’ for poor, sick children, in addition to helping with the construction of a new wing of the hospital. This essay does not analyze how Aunt Judy’s Magazine helped the hospital but investigates the ways the ‘Correspondence’ pages were used for the ideological work of creating a new generation of middle-class philanthropists. The analysis of the correspondence pages of Aunt Judy’s Magazine reveals how the conversational tone of the fictional persona of ‘Aunt Judy’ helped build a trusting relationship with the child readers which was instrumental in recruiting them to fight the ‘Grim Nurses’.